Identification of Genes Regulating Gene Targeting by a High-Throughput Screening Approach - Fabien Delacôte; Christophe Perez; Valérie Guyot; Catherine Mikonio; Pierrick Potrel; Jean-Pierre Cabaniols; Christophe Delenda; Frédéric Pâques; Philippe Duchateau (Journal of Nucleic Acids)
Homologous gene targeting (HGT) is a precise but inefficient process for genome engineering. Several methods for increasing its efficiency have been developed, including the use of rare cutting endonucleases. However, there is still room for improvement, as even nuclease-induced HGT may vary in efficiency as a function of the nuclease, target site, and cell type considered. We have developed a high-throughput screening assay for the identification of factors stimulating meganuclease-induced HGT. We used this assay to explore a collection of siRNAs targeting 19,121 human genes. At the end of secondary screening, we had identified 64 genes for which knockdown affected nuclease-induced HGT. Two of the strongest candidates were characterized further. We showed that siRNAs directed against the ATF7IP gene, encoding a protein involved in chromatin remodeling, stimulated HGT by a factor of three to eight, at various loci and in different cell types. This method thus led to the identification of a number of genes, the manipulation of which might increase rates of targeted recombination.